Anti-calcitonin gene-related peptide monoclonal antibodies for the treatment of vestibular migraine: A prospective observational cohort study - Russo, Cinzia Valeria; Saccà, Francesco; Braca, Simone; Sansone, Mattia; Miele, Angelo; Stornaiuolo, Antonio; De Simone, Roberto (Cephalalgia, 2023)
Vestibular migraine is considered the most common cause of recurrent vertigo for which specific treatments are missing. Monoclonal antibodies against calcitonin gene-related peptide,, are effective in preventing migraine. Since CGRP is also detected in human cochlear and vestibular organs it may also play a role in vestibular physiology. This is a prospective observational cohort study, aiming at evaluating the efficacy of erenumab, fremanezumab or galcanezumab for the treatment of fifty vestibular migraine patients. We assessed mean monthly days with headache and dizziness/vestibular symptoms, pain intensity and migraine-related clinical burden occurring for 18 months. Response to treatment was excellent as 45 (90%) patients had at least a 50% reduction in vertigo frequency, 43 (86%) had at least a 50% reduction in headache frequency, and 40 (80%) a MIDAS reduction of at least 50%. Overall, 39 (78%) patients had a concomitant reduction of all three parameters. Mean monthly days with dizziness/vestibular symptoms showed an overall significant decrease from a mean of 10.3 ± 1.9 at baseline to 0.8 ± 0.3 days, difference 9.5 (CI 95% 3.6, 15.4; p < 0.001) after twelve months. We show that anti-CGRP mAbs may be effective in the treatment of Vestibular Migraine. Their use should be encouraged early in the disease course to allow for a better symptom control and quality of life improvement.